1983
DOI: 10.1002/j.1875-9114.1983.tb04546.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Beta‐Adrenergic Blocking Agents in Anxiety Disorders and Schizophrenia

Abstract: In the 1960s, several studies reported that propranolol and other beta‐blocking drugs appeared especially useful in patients with physical symptoms of anxiety. However, subsequent reports produced conflicting findings, and at this time the efficacy of propranolol in anxiety disorders is not clearly established. Propranolol's utility in anxiety states may be entirely restricted to those anxiety patients whose physical symptoms have not adequately responded to benzodiazepine therapy. This places the beta‐blocker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The use of fl-adrenergic blocking drugs in the treatment of mental disorders began in 1966 when Granville-Grossman and Turner (1966) suggested that propranolol might be beneficial in managing the physical symptoms of anxiety, especially cardiovascular complaints. Additional reports evaluating the efficacy of fl-blockers in anxiety Address for correspondence: Dr. Peggy E. Hayes, Medical College of Virginia, School of Pharmacy, Box 581 MCV Station, Richmond, VA 23298, U.S.A. states (Wheatley 1969;Bonn et al 1972;Ramsey et al 1973;Tyrer andLader 1973, 1974a, b;Kellner et al 1974;Silverstone 1974;Becker 1976;Burrows et al 1976;Johnson et al 1976;Tanna et al 1977;Kathol et al 1980) and panic disorder (Noyes et al 1984;Shehi and Patterson 1984;Munjack et al 1985) have been published and several review articles have been written (Whitlock and Price 1974;Greenblatt and Shader 1978;Cole et al 1979;Tyrer 1980;Noyes 1982Noyes , 1985Hayes and Schulz 1983). However, the efficacy and exact therapeutic role of /3-blocking drugs in treating generalized anxiety disorder and panic disorder 0165-0327/87/$03.50 ,~ 1987 Elsevier Science Publishers B.V. (Biomedical Division) remain unestablished.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fl-adrenergic blocking drugs in the treatment of mental disorders began in 1966 when Granville-Grossman and Turner (1966) suggested that propranolol might be beneficial in managing the physical symptoms of anxiety, especially cardiovascular complaints. Additional reports evaluating the efficacy of fl-blockers in anxiety Address for correspondence: Dr. Peggy E. Hayes, Medical College of Virginia, School of Pharmacy, Box 581 MCV Station, Richmond, VA 23298, U.S.A. states (Wheatley 1969;Bonn et al 1972;Ramsey et al 1973;Tyrer andLader 1973, 1974a, b;Kellner et al 1974;Silverstone 1974;Becker 1976;Burrows et al 1976;Johnson et al 1976;Tanna et al 1977;Kathol et al 1980) and panic disorder (Noyes et al 1984;Shehi and Patterson 1984;Munjack et al 1985) have been published and several review articles have been written (Whitlock and Price 1974;Greenblatt and Shader 1978;Cole et al 1979;Tyrer 1980;Noyes 1982Noyes , 1985Hayes and Schulz 1983). However, the efficacy and exact therapeutic role of /3-blocking drugs in treating generalized anxiety disorder and panic disorder 0165-0327/87/$03.50 ,~ 1987 Elsevier Science Publishers B.V. (Biomedical Division) remain unestablished.…”
Section: Introductionmentioning
confidence: 99%
“…tors, supplemented by a presynaptic attenuation of ßreceptor mediated doparnine release should result in an effective suppression of dopaminergic hyperactivity without the disadvantages of a total postsynaptic DA 2 -receptor blockade. This hypothesis is supported by the intensive discussion of the role of impaired adrenergic transmission in schizophrenia (Van Kammen and Antelman, 1984), by clinical resuIts (Hayes and Schulz, 1983), and by reports on a beneficial effect ofß-blockers against neuroleptic induced tardive dyskinesia (Karniol and Portela, 1982; O/ivera and Kiefer, 1984).…”
Section: Discussionmentioning
confidence: 91%
“…Timelotem «±)-1O-fluoro-I ,2,3,4,4a,5-hexahydro-3-methyl-7-(2-thienyl)-pyrazino[ I , [1,4] benzodiazepine dimaleate; internal code no. KC 7507) is a representative of a newly developed class of [I ,2]-anellated [1,4] benzodiazepines which have lost the typical minor tranquilizer properties, but can be characterized as antipsychotics (Liepmann et al, 1984;Ruh/and et al, 1985). The CNS pharrnacological profile of timelotem (TIM) was evaluated by means of in vitro receptor binding methods and various in vivo tests in animals, indicative for antipsychotic properties and typical neuroleptic side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, diazepam proved to be more effective in those psychic aspects of the cardiac neurosis syndrome not directly related to the hyperdynamic beta-adrenergic state [35][36][37]. The anxiolytic effect of beta blockers might be related to their peripheral action without direct influence on the central nervous system, as documented for diazepam and other benzodiazepines [38][39][40]. The different central action of the two drugs is demonstrated by the results of acoustic and visual tests, showing lengthening of the reaction times with diazepam but not with bisoprolol, which did not negatively affect patients' central nervous functions.…”
Section: Discussionmentioning
confidence: 99%